The Development of Problem-Based Learning LKPD to Improve Students’ Critical Thinking Ability in The Fifth Grade of Primary School - Cici Nur Azizah; Arwin Surbakti; Pargito Pargito (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
The objective of the study is to create a PBL-based LKPD product that is feasible to improve critical thinking skills and determine the effectiveness of PBL-based LKPD products in enhancing critical thinking skills using T-test value analysis from pretest and posttest data. The research was conducted in the fifth grade of SD Negeri 4 Candimas consisting of 33 students. The type of study used Research and Development (R&D) carried out referring to the Borg & Gall design model. The results of this study were following the results of the development feasibility test to get results > 86, so it can be categorized as very good. In the t-test value, the value of Sig. (2-tailed) of 0.000 <0.05, so as the basis for decision making in the independent sample t-test, it can be concluded that H0 was rejected and H1 was accepted. Thus, it is concluded that the implementation of PBL-based LKPD is effectively used to improve students' critical thinking skills.